Histopathology overview of tilapia (Oreochromis mossambicus) liver organs contaminated by lead metal (Pb) in Lake Tempe, Wajo Regency. Issue 1 (October 2021) - Jabbar, R A; Sari, D K; Tahir, A
Abstract: Tilapia fish ( Oreochromis mossambicus ) is one of the most popular freshwater fish in the community because it is easy to breed and its survival is high and group. The purpose of this study was to determine the histopathology of the liver in tilapia fish contaminated with lead heavy metal (Pb) in Lake Tempe, Wajo Regency. This research was conducted in March to June 2020. The number of fish samples used in this study was 21 fish. Measurement of lead heavy metal content (Pb) contained in the liver of tilapia fish ( Oreochromis mossambicus ). Measurement of heavy metal content was carried out with Atomic Absorption Spectrophotometer and obtained lead metal content (Pb) <0.14-2.8 µg / g with an average of 0.82 ± 0.83 µg / g. Preparation of liver organ fixation using 10% neutral buffered formalin (NFB), multilevel alcohol is used for dehydration, embedding using parafifin and haematoxylin-eosin staining. Analysis of the data used is descriptive qualitative. This research shows that lead metal (Pb) causes damage to the liver of tilapia fish. Damage to the liver in the form of inflammatory cell infiltration, fat degeneration, haemorrhage and necrosis. Damage that occurred as a result exposure to heavy metals, dissolved in the aquatic ecosystem that passed the threshold limit.